Characterizing memory loss in patients with autoimmune limbic encephalitis hippocampal lesions. Issue 11 (31st August 2019) - Lad, Meher; Mullally, Sinéad L.; Houston, Alexandra L.; Kelly, Tom; Griffiths, Timothy D.
Abstract: Since the publication of Scoville and Milner's (1957) seminal paper, the precise functional role played by the hippocampus in support of human memory has been fiercely debated. For instance, the single question of whether the hippocampus plays a time‐limited or an indelible role in the recollection of personal memories led to a deep and tenacious schism within the field. Similar polarizations arose between those who debated the precise nature of the role played by the hippocampus in support of semantic relative to episodic memories and in recall/recollection relative to familiarity‐based recognition. At the epicenter of these divisions lies conflicting neuropsychological findings. These differences likely arise due to the consistent use of heterogeneous patient populations to adjudicate between these positions. Here we utilized traditional neuropsychological measures in a homogenous patient population with a highly discrete hippocampal lesion (i.e., VGKCC‐Ab related autoimmune limbic encephalitis patients). We observed consistent impairment of recent episodic memories, a present but less striking impairment of remote episodic memories, preservation of personal semantic memory, and recall but not recognition memory deficits. We conclude that this increasingly well‐characterized patient group may represent an important homogeneous population in which the functional role played by the hippocampus may be more precisely delineated.